The relationship between occupational stress and organisational commitment among police officers in Sebokeng Cluster - Kgopotso, Mashego Rizeth (Vaal University of Technology, 2013)
The purpose of this study was to investigate the relationship between occupational stress and organisational commitment among police officers in the Sebokeng Cluster. To this end, occupational stress and organisational commitment of police officers were assessed. The review of the literature presupposes three source of occupational stress, namely, role overload, role ambiguity and role conflict and their hypothesized influence over or relationship with organisational commitment factors. The literature also indicates that there are three dimensions of organisational commitment: affective commitment, continuance commitment and normative commitment. The research design used in this study is qualitative research design. In this study a survey was used to collect data from 267 respondents. The Statistical Package for Social Science version 21.0 was used to analyse the data. The response rate was 199 (75%) of the total sample. Statistical techniques such as Pearson's correlation coefficient analysis, frequency analysis, factor analysis (Kaiser-Meyer Olkin and Bartlett's test of sphericity) and means scores were used to analyse data. The Pearson's coefficient revealed that the relationship between occupational stress and organisational commitment was found to be low and weak. The level of occupational stress experienced by police officers in the Sebokeng Cluster was found to be low. In similar vein, police officers had organisational commitment to the police agency. The Sebokeng Cluster management can utilise the research findings to formulate appropriate strategies to constantly reduce the occupational stress and to improve organisational commitment among police officers. In order to deal effectively with problems of occupational stress, management in Sebokeng Cluster should provide a safe physical work environment and ensure provision of resources and materials for execution of duties. Furthermore, they should encourage healthy lifestyle for employees.
M. Tech. (Department of Human Resource Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Occupational stress; Organisational commitment; Police officers; Sebokeng Cluster; Dissertations, Academic -- South Africa.; Job stress.; Organizational commitment.; Police -- South Africa.; Lifestyles--Health aspects.